School‐Based Sex Education and Neuroscience: What We Know About Sex, Romance, Marriage, and Adolescent Brain Development1. (August 2015) - Ballonoff Suleiman, Ahna; Johnson, Megan; Shirtcliff, Elizabeth A.; Galván, Adriana
ABSTRACT BACKGROUND Many school‐based abstinence‐only sex education curricula state that sexual activity outside of marriage is likely to have harmful psychological effects. Recent advances in neuroscience have expanded our understanding of the neural underpinnings of romantic love, marriage, sexual desire, and sexual behavior and improved our understanding of adolescent brain development. METHODS In this article, we review recent advances in neuroscience and clarify what is known about the link between neural development and adolescent romantic and sexual behavior and what opportunities exist for future research. RESULTS Whereas the evidence from neuroscience does not yet allow for clear conclusions about the cost or benefits of early romantic relationships and sexual behavior, it does indicate that providing developmentally appropriate education contributes to lifelong sexual health. CONCLUSIONS Developing policies and practices for school‐based sex education that reflect current research will best support the sexual and reproductive health of adolescents throughout their lives.